Food plant engineering systems - Robberts, Theunis C. (CRC Press, 2013)
The component parts of a manufacturing system are important. Without peripherals and services such as pumps, boilers, power transmission, water treatment, waste disposal, and efficient lighting, the system will collapse. Food Plant Engineering Systems, Second Edition fills the need for a reference dealing with the bits and pieces that keep systems running, and also with how the peripheral parts of a processing plant fit within the bigger picture.